Environment-friendly anthraquinone hydrogenation catalyst and preparation method thereof

CN122605512BActive Publication Date: 2026-10-20YANTAI BAICHUAN HUITONG TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202611105677.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-20
Estimated Expiration
2046-07-24

AI Technical Summary

Benefits of technology

(1)本发明将葡萄糖与铝盐预混、支化聚乙烯亚胺与偏铝酸盐预混,再通过将偏铝酸盐混合溶液滴加到铝盐混合溶液中实现共沉淀并最终煅烧制备氧化铝载体。锚定在铝源上的葡萄糖倾向于嵌入正在形成的无机颗粒内部,而被静电吸附在聚乙烯亚胺链上的偏铝酸根离子则倾向于在颗粒外围反应沉积。在随后的洗涤、干燥与煅烧阶段,这种空间分步的复合结构被固化,并随着模板的去除,留下相应的孔道。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application belongs to the technical field of catalysts, and particularly relates to an environmentally-friendly anthraquinone hydrogenation catalyst and a preparation method thereof. The preparation method of the catalyst comprises the following steps: (1) preparing an aluminum salt mixed solution containing aluminum salt and glucose; (2) preparing a meta-aluminite mixed solution containing meta-aluminite and branched polyethyleneimine; (3) obtaining a catalyst carrier through a co-precipitation-calcination process; (4) impregnating the catalyst carrier with a palladium salt solution; and (5) obtaining the environmentally-friendly anthraquinone hydrogenation catalyst after drying, calcination and reduction. In the application, inexpensive and readily available glucose is used as a template agent, and branched polyethyleneimine is added to solve the defects of the alumina carrier prepared by using small-molecule glucose as a template, i.e., low specific surface area and small pore size, and a catalyst carrier with a high specific surface area is successfully prepared. The catalyst carrier is impregnated with metal palladium, which significantly reduces the preparation cost of the anthraquinone hydrogenation catalyst, has the advantages of simple preparation process, green environmental protection and the like, and is easy to realize large-scale preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst technology, specifically relating to an environmentally friendly anthraquinone hydrogenation catalyst and its preparation method. Background Technology

[0002] Hydrogen peroxide, commonly known as hydrogen peroxide solution, is a very important green fine chemical in industry. Under normal temperature and pressure conditions, hydrogen peroxide is a colorless and transparent liquid, miscible with water in any proportion. Because hydrogen peroxide only produces oxygen and water molecules during use and does not pollute the environment, it is an environmentally friendly green chemical product. Due to its excellent oxidizing and environmentally friendly properties, it is widely used in environmental protection, green organic synthesis, medical disinfection, papermaking, textiles, aerospace, and many other industries.

[0003] Hydrogen peroxide, as a widely used and environmentally friendly inorganic chemical raw material and green basic chemical, has attracted much attention, and its demand is showing a continuous upward trend. Researching how to efficiently, economically, and safely prepare hydrogen peroxide, improving preparation methods, and exploring new preparation routes have become key concerns for researchers. Since its discovery, numerous different industrial production methods for hydrogen peroxide have been developed, such as inorganic chemical reaction methods, electrolysis, isopropanol methods, cathode-anodic reduction methods, direct hydrogen-oxygen synthesis methods, and anthraquinone methods. The anthraquinone method, due to its mature production technology and ease of large-scale scalability, has become the most widely used preparation method for hydrogen peroxide.

[0004] Since its initial industrial production of hydrogen peroxide by Fischer in the 1940s, the anthraquinone process has undergone numerous improvements, resulting in a more mature production technology. However, the basic process still involves the hydrogenation reaction of anthraquinone derivatives, the oxidation reaction of the working fluid, and the extraction and purification of hydrogen peroxide. Among these, the hydrogenation reaction of anthraquinone derivatives is the core and key step in the entire production process, and the performance of the hydrogenation catalyst determines the output efficiency and product quality of the equipment, directly affecting the economic benefits of this method.

[0005] The anthraquinone hydrogenation reaction is the most critical step in the anthraquinone process for producing hydrogen peroxide, and the research on hydrogenation catalysts plays a vital role, as the performance of the hydrogenation catalyst largely determines the production capacity and cost of the equipment. Therefore, researching hydrogenation catalysts with high activity, high selectivity, and low cost has significant research importance and commercial value. For example, Chinese invention patent application CN112717925A discloses an anthraquinone hydrogenation catalyst, its preparation method, and its application. The anthraquinone hydrogenation catalyst contains a Group VIIIB noble metal and boron-modified alumina. Based on the mass of the boron-modified alumina, the boron content (in elemental) is 0.1-5%, preferably 0.5-2%. Based on the mass of the final anthraquinone hydrogenation catalyst, the Group VIIIB noble metal content is 0.1-2%, preferably 0.15-0.25%. This anthraquinone hydrogenation catalyst has advantages such as low active metal content and minimal metal loss. However, the aforementioned patent application uses boron to modify the alumina support, resulting in a complex process; furthermore, the product has low hydrogenation efficiency, making widespread application difficult. Summary of the Invention

[0006] The purpose of this invention is to provide an environmentally friendly anthraquinone hydrogenation catalyst and its preparation method. It uses inexpensive and readily available glucose as the main template agent and adds a small amount of branched polyethyleneimine to prepare an alumina catalyst support with high specific surface area and large pore size. The active component is impregnated with the alumina to improve the hydrogenation efficiency, and it has the advantages of low energy consumption, good economy and green environmental protection.

[0007] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing an environmentally friendly anthraquinone hydrogenation catalyst includes the following steps: (1) Add aluminum salt and glucose to deionized water and stir until homogeneous to obtain a mixed aluminum salt solution; (2) Add aluminate and branched polyethyleneimine to deionized water and stir until homogeneous to obtain a mixed solution of aluminate; the mass ratio of branched polyethyleneimine to glucose is (0.1-0.25):1; (3) While stirring, the aluminate mixture solution is added dropwise to the aluminum salt mixture solution to obtain the final solution, and the pH of the final solution is adjusted to be alkaline; the reaction is heated, and then the catalyst support is obtained through filtration, washing, drying and calcination. (4) Disperse the palladium salt in a solvent to obtain a palladium salt solution, and then impregnate the catalyst support with the palladium salt solution; (5) The impregnated catalyst support is dried, calcined and reduced to obtain an environmentally friendly anthraquinone hydrogenation catalyst.

[0008] This invention involves premixing glucose with aluminum salts and branched polyethyleneimine with aluminate, then co-precipitating the alumina catalyst support by dropwise adding the aluminate mixture to the aluminum salt mixture, followed by calcination. First, glucose, being a short-chain molecule with a small molecular weight, contains abundant hydroxyl groups during the glucose-aluminate premixing step. These hydroxyl groups can complex with aluminum ions or form hydrogen bond networks. This process uniformly anchors glucose molecules around the aluminum source at the molecular level, facilitating subsequent uniform precipitation. During the branched polyethyleneimine-aluminate premixing step, negatively charged aluminate ions are adsorbed and enriched around the positively charged polyethyleneimine molecular chains through electrostatic attraction, forming polyelectrolyte-inorganic ion complex micelles, promoting system stability. Subsequently, during the dropwise addition of the aluminate mixture to the aluminum salt mixture, a localized neutralization reaction occurs at the interface, where aluminate ions react with aluminum ions to form a precursor precipitate. Since glucose is pre-anchored in the aluminum salt solution, and branched polyethyleneimine is carried in from the inside of the droplets along with aluminate ions, the newly formed precursor precipitate particles are simultaneously constrained by both templates. Specifically, glucose anchored to the aluminum source tends to embed inside the forming inorganic particles, while aluminate ions electrostatically adsorbed on the polyethyleneimine chains tend to react and deposit on the periphery of the particles. In the subsequent washing, drying, and calcination stages, this spatially distributed composite structure is solidified, leaving corresponding channels as the templates are removed.

[0009] Chinese invention patent applications CN120515404A and CN120438003A previously used long-chain alkyl quaternary ammonium salts and polyvinylpyrrolidone as template agents to prepare alumina catalyst supports. However, the cost of these raw materials is relatively high, making it difficult to promote their use.

[0010] In the process of this invention, glucose is relatively inexpensive and serves as the main template responsible for constructing fine mesopores to maintain a high specific surface area. Branched polyethyleneimine, as an additive, expands the space between or within particles to increase the pore size. The division of labor and cooperation in the spatial distribution of the two allows the calcined alumina to possess both the high specific surface area contributed by the glucose template and the large pore size contributed by the branched polyethyleneimine additive.

[0011] Furthermore, this process possesses significant potential for industrial applications. Glucose and branched polyethyleneimine are both bulk industrial chemicals with relatively controllable costs. The entire preparation process is based on conventional co-precipitation, washing, drying, and calcination unit operations, exhibiting good compatibility with existing alumina industrial production lines. It eliminates the need for additional high-pressure or supercritical equipment, facilitating technology scale-up and transformation, and providing a feasible technical route for the low-cost preparation of high-performance catalysts.

[0012] In one embodiment, the aluminum salt in step (1) is at least one of aluminum nitrate, aluminum chloride, and aluminum sulfate; the concentration of aluminum salt in the aluminum salt mixed solution is 10-40 g / L.

[0013] In one embodiment, the mass ratio of glucose to aluminum salt in step (1) is (0.1-0.3):1. Specifically, the mass ratio of glucose to aluminum salt can be 0.1:1, 0.15:1, 0.2:1, 0.25:1, or 0.3:1. More specifically, the mass ratio of glucose to aluminum salt is (0.15-0.25):1. Using an appropriate amount of glucose can effectively serve as a template while avoiding problems such as weakening the carrier strength due to excessive glucose use, pore collapse during calcination, and reduced specific surface area.

[0014] In one embodiment, the aluminate in step (2) is at least one of sodium aluminate or potassium aluminate; the concentration of aluminate in the aluminate mixed solution is 5-25 g / L.

[0015] In one embodiment, in step (2), the aluminate mixed solution can be appropriately heated to accelerate the dispersion of branched polyethyleneimine. The branched polyethyleneimine can be selected from those with good solubility and a weight-average molecular weight of 500-5000. More specifically, at least one of the following weight-average molecular weights can be selected: 600 (PEI 600), 800 (PEI 800), 1200 (PEI 1200), 1500 (PEI 1500), 1800 (PEI 1800), 2000 (PEI 2000), 3000 (PEI 3000), 4000 (PEI 4000), and 5000 (PEI 5000). If the molecular weight is too small, it is not easy to promote the dispersion of the precipitate; if the molecular weight is too large, it will affect the template effect of small molecule glucose after mixing, which is not conducive to the formation of porous structures. In particular, a branched polyethyleneimine with a weight-average molecular weight of 1000-3000 can be selected. The reason why branched polyethyleneimine was chosen over nonlinear polyethyleneimine in this invention is that branched polyethyleneimine has a unique three-dimensional dendritic molecular configuration, with a large number of primary, secondary, and tertiary amine groups exposed on its surface, and good water solubility; while linear polyethyleneimine has a straight-chain structure, poor solubility, and higher cost. The branched structure means that a large number of branch ends are distributed on a single molecular chain, and each end contains a primary amine group. This compact and highly branched three-dimensional configuration makes it present a randomly coiled spherical or quasi-spherical conformation in solution, rather than the extended chain conformation of the nonlinear molecule. Furthermore, the branched polyethyleneimine in step (2) can be composed of two branched polyethyleneimines with different molecular weights. By selecting two branched polyethyleneimines with different molecular weights as promoters, the role of branching promoters can be better utilized, and the specific surface area of ​​the prepared catalyst support can be increased. When branched polyethyleneimine is adsorbed on the surface of precursor particles, its three-dimensional configuration can form an effective physical isolation layer between particles, preventing hard agglomeration of nanoparticles through steric hindrance effect. In contrast, linear polyethyleneimine tends to form extended chain conformations in solution, potentially bridging multiple particles simultaneously during adsorption. This can easily induce particle aggregation and sedimentation, hindering the high dispersion of the precursor. Furthermore, since branched polyethyleneimine is mainly distributed on the periphery of the particles, its decomposition process can modify the support surface in situ, potentially introducing surface defects or regulating surface acidity / alkalinity. For the anthraquinone hydrogenation reaction, suitable support surface properties contribute to the high dispersion loading of palladium metal and improve the selectivity of the target product, hydrogen peroxide.

[0016] In one embodiment, the mass ratio of branched polyethyleneimine to glucose in step (2) is (0.15-0.25):1. Specifically, it can be 0.15:1, 0.18:1, 0.2:1, 0.22:1, 0.24:1, or 0.25:1. Branched polyethyleneimine and glucose act as a dual template in this invention. When PEI is in excess relative to glucose, due to the strong electrostatic and hydrogen bonding between the densely packed amino groups on its molecular chain and the aluminum precursor and glucose, branched polyethyleneimine tends to preferentially adsorb aluminum species and dominate the deposition process. This weakens the relative role of the glucose template, destroys the mesoporous structure originally guided by glucose, results in poor stability, and causes collapse during calcination, which is detrimental to increasing the specific surface area.

[0017] In one embodiment, the mass ratio of aluminate in step (2) to aluminum salt in step (1) is (0.1-1):1. When preparing the solution, the solution can be heated to promote the dissolution and dispersion of each raw material component.

[0018] In one embodiment, in step (3), the aluminum salt mixed solution can be heated to 50-70°C first, and then the aluminate mixed solution can be added dropwise to promote the dispersion of each component; the dropping rate is 5-15 mL / min.

[0019] In one embodiment, the pH value in step (3) is 8-11; the heating reaction temperature is 80-90℃, and the heating reaction time is 1-3h; the calcination temperature is 550-650℃, and the calcination time is 4-6h. The method of adjusting the pH is not particularly limited and can be achieved by adding an acid or alkali. Specifically, an acidic substance such as hydrochloric acid, sulfuric acid, or nitric acid, or an alkaline substance such as sodium hydroxide, potassium hydroxide, or ammonia water can be used for adjustment.

[0020] In one embodiment, the palladium salt in step (4) is at least one of palladium chloride, palladium nitrate, and palladium acetate. The solvent type is not particularly limited; acetone, a common organic solvent in the art, can be used.

[0021] In one embodiment, the impregnation in step (4) employs an equal-volume impregnation process. The equal-volume impregnation process allows for more precise control of the solution volume, facilitating adjustment of the palladium loading. Furthermore, multiple equal-volume impregnation processes can be used.

[0022] In one embodiment, step (4) involves preparing a palladium salt solution with a palladium loading of 0.1-1 wt% in the catalyst support.

[0023] In one embodiment, the drying temperature in step (5) is 100-130°C.

[0024] In one embodiment, the calcination temperature in step (5) is 300-350°C and the calcination time is 3-4 hours.

[0025] In one embodiment, the reduction in step (5) is carried out by using a 10 vol% hydrogen / argon mixture at 160-200°C for 2.5-3.5 h.

[0026] On the other hand, the present invention also provides an environmentally friendly anthraquinone hydrogenation catalyst prepared by the above method. Using readily available and inexpensive glucose and branched polyethyleneimine as composite template agents, a catalyst support with a high specific surface area was prepared. Impregnating this support with palladium significantly reduces the preparation cost of the anthraquinone hydrogenation catalyst and has advantages such as simple and environmentally friendly preparation process, making it easy to achieve large-scale preparation.

[0027] Beneficial effects: (1) In this invention, glucose is premixed with aluminum salt, and branched polyethyleneimine is premixed with aluminate. Then, the aluminate mixture is added dropwise to the aluminum salt mixture to achieve co-precipitation, followed by calcination to prepare an alumina support. Glucose anchored to the aluminum source tends to embed inside the forming inorganic particles, while aluminate ions electrostatically adsorbed on the polyethyleneimine chains tend to react and deposit on the periphery of the particles. In the subsequent washing, drying, and calcination stages, this spatially stepwise composite structure is solidified, leaving corresponding channels as the template is removed.

[0028] (2) Using inexpensive and readily available glucose as a template agent, the defects of low specific surface area and small pore size of alumina support prepared with small molecule glucose as template were solved by adding branched polyethyleneimine as an auxiliary agent. A catalyst support with high specific surface area was successfully prepared. The preparation cost of anthraquinone hydrogenation catalyst was significantly reduced by impregnating the support with palladium. It also has the advantages of simple preparation process and green technology, and is easy to scale up. Detailed Implementation

[0029] The embodiments described are provided to better illustrate the present invention, but are not intended to limit the scope of the invention to the embodiments described. Therefore, non-essential improvements and adjustments made to the embodiments by those skilled in the art based on the above description are still within the scope of protection of the present invention.

[0030] Performance testing: Catalyst support performance: The specific surface area (m²) of the catalyst supports prepared in Examples 1-10 and Comparative Examples 1-2 was tested by gas adsorption (BET) method. 2 (g) and pore size (nm).

[0031] Performance of the environmentally friendly anthraquinone hydrogenation catalyst: 2-Ethylanthraquinone was dissolved in a mixed solvent of 1,2,4-trimethylbenzene and trioctyl phosphate (volume ratio of 1:1) to prepare a working solution with a concentration of 120 g / L. 60 mL of the working solution and 1 g of the environmentally friendly anthraquinone hydrogenation catalyst were added to a reactor. High-purity hydrogen was used as the feedstock, and the reaction temperature was set at 60℃, the reaction pressure at 0.3 MPa, and the reaction time at 90 min. The reacted working solution was oxidized by purging with oxygen, and the hydrogen peroxide content in the working solution was analyzed by titration with potassium permanganate solution to calculate the hydrogenation efficiency (g / L).

[0032] Example 1 A method for preparing an environmentally friendly anthraquinone hydrogenation catalyst includes the following steps: (1) Add aluminum nitrate and glucose to deionized water and stir until homogeneous to obtain a mixed aluminum nitrate solution; the concentration of aluminum nitrate in the mixed aluminum nitrate solution is 20 g / L; the mass ratio of glucose to aluminum nitrate is 0.1:1; (2) Add sodium aluminate and branched polyethyleneimine PEI 600 to deionized water and stir until homogeneous to obtain a sodium aluminate mixed solution; the mass ratio of branched polyethyleneimine to glucose is 0.25:1; the concentration of sodium aluminate in the sodium aluminate mixed solution is 12 g / L; the mass ratio of sodium aluminate to aluminum nitrate in step (1) is 0.75:1; (3) First, heat the aluminum nitrate mixed solution to 62°C, and while stirring, add the sodium aluminate mixed solution dropwise to the aluminum nitrate mixed solution at a rate of 10 mL / min to obtain the final solution, and adjust the pH of the final solution to 10; heat the reaction at 90°C for 1.6 h, then filter, wash, dry, and calcine at 630°C for 4 h to obtain the catalyst support; (4) Prepare a palladium salt solution with a palladium loading of 0.2 wt% in the catalyst support. Specifically, disperse palladium acetate in acetone to obtain a palladium salt solution, and then impregnate the catalyst support with the palladium salt solution using an equal volume impregnation process. (5) The impregnated catalyst support was dried at 110℃, calcined at 330℃ for 3 hours, and then reduced at 180℃ for 3 hours using a 10 vol% hydrogen / argon mixture to obtain the environmentally friendly anthraquinone hydrogenation catalyst. The specific surface area of ​​the catalyst support was tested to be 278 m². 2 / g, with a pore size of 16.24nm; the environmentally friendly anthraquinone hydrogenation catalyst has a hydrogenation efficiency of 11.17g / L.

[0033] Example 2 A method for preparing an environmentally friendly anthraquinone hydrogenation catalyst includes the following steps: (1) Add aluminum nitrate and glucose to deionized water and stir until homogeneous to obtain a mixed aluminum nitrate solution; the concentration of aluminum nitrate in the mixed aluminum nitrate solution is 20 g / L; the mass ratio of glucose to aluminum nitrate is 0.26:1; (2) Add sodium aluminate and branched polyethyleneimine PEI 3000 to deionized water and stir until homogeneous to obtain a sodium aluminate mixed solution; the mass ratio of branched polyethyleneimine to glucose is 0.1:1; the concentration of sodium aluminate in the sodium aluminate mixed solution is 12 g / L; the mass ratio of sodium aluminate to aluminum nitrate in step (1) is 0.75:1; (3) First, heat the aluminum nitrate mixed solution to 62°C, and while stirring, add the sodium aluminate mixed solution dropwise to the aluminum nitrate mixed solution at a rate of 10 mL / min to obtain the final solution, and adjust the pH of the final solution to 10.5; heat the reaction at 80°C for 3 h, then filter, wash, dry, and calcine at 580°C for 6 h to obtain the catalyst support; (4) Prepare a palladium salt solution with a palladium loading of 0.2 wt% in the catalyst support. Specifically, disperse palladium acetate in acetone to obtain a palladium salt solution, and then impregnate the catalyst support with the palladium salt solution using an equal volume impregnation process. (5) The impregnated catalyst support was dried at 110℃, calcined at 310℃ for 4 hours, and then reduced at 180℃ for 3 hours using a 10 vol% hydrogen / argon mixture to obtain the environmentally friendly anthraquinone hydrogenation catalyst. The specific surface area of ​​the catalyst support was tested to be 293 m². 2 / g, with a pore size of 17.21nm; the environmentally friendly anthraquinone hydrogenation catalyst has a hydrogenation efficiency of 12.52g / L.

[0034] Example 3 A method for preparing an environmentally friendly anthraquinone hydrogenation catalyst includes the following steps: (1) Add aluminum nitrate and glucose to deionized water and stir until homogeneous to obtain a mixed aluminum nitrate solution; the concentration of aluminum nitrate in the mixed aluminum nitrate solution is 20 g / L; the mass ratio of glucose to aluminum nitrate is 0.3:1; (2) Add sodium aluminate and branched polyethyleneimine (a mixture of PEI 800 and PEI 1800 in a mass ratio of 1:1) to deionized water and stir until homogeneous to obtain a sodium aluminate mixed solution; the mass ratio of branched polyethyleneimine to glucose is 0.2:1; the concentration of sodium aluminate in the sodium aluminate mixed solution is 12 g / L; the mass ratio of sodium aluminate to aluminum nitrate in step (1) is 0.75:1; (3) First, heat the aluminum nitrate mixed solution to 62°C, and while stirring, add the sodium aluminate mixed solution dropwise to the aluminum nitrate mixed solution at a rate of 10 mL / min to obtain the final solution, and adjust the pH of the final solution to 10; heat the reaction at 85°C for 2 h, then filter, wash, dry, and calcine at 600°C for 5 h to obtain the catalyst support; (4) Prepare a palladium salt solution with a palladium loading of 0.2 wt% in the catalyst support. Specifically, disperse palladium acetate in acetone to obtain a palladium salt solution, and then impregnate the catalyst support with the palladium salt solution using an equal volume impregnation process. (5) The impregnated catalyst support was dried at 110℃, calcined at 340℃ for 3 hours, and then reduced at 180℃ for 3 hours using a 10 vol% hydrogen / argon mixture to obtain the environmentally friendly anthraquinone hydrogenation catalyst. The specific surface area of ​​the catalyst support was tested to be 281 m². 2 / g, with a pore size of 17.33nm; the environmentally friendly anthraquinone hydrogenation catalyst has a hydrogenation efficiency of 12.19g / L.

[0035] Example 4 A method for preparing an environmentally friendly anthraquinone hydrogenation catalyst includes the following steps: (1) Add aluminum nitrate and glucose to deionized water and stir until homogeneous to obtain a mixed aluminum nitrate solution; the concentration of aluminum nitrate in the mixed aluminum nitrate solution is 20 g / L; the mass ratio of glucose to aluminum nitrate is 0.12:1; (2) Add sodium aluminate and branched polyethyleneimine PEI 1200 to deionized water and stir until homogeneous to obtain a sodium aluminate mixed solution; the mass ratio of branched polyethyleneimine to glucose is 0.23:1; the concentration of sodium aluminate in the sodium aluminate mixed solution is 12 g / L; the mass ratio of sodium aluminate to aluminum nitrate in step (1) is 0.75:1; (3) First, heat the aluminum nitrate mixed solution to 62°C, and while stirring, add the sodium aluminate mixed solution dropwise to the aluminum nitrate mixed solution at a rate of 10 mL / min to obtain the final solution, and adjust the pH of the final solution to 10; heat the reaction at 82°C for 1.8 h, then filter, wash, dry, and calcine at 590°C for 5.5 h to obtain the catalyst support; (4) Prepare a palladium salt solution with a palladium loading of 0.2 wt% in the catalyst support. Specifically, disperse palladium acetate in acetone to obtain a palladium salt solution, and then impregnate the catalyst support with the palladium salt solution using an equal volume impregnation process. (5) The impregnated catalyst support was dried at 110℃, calcined at 310℃ for 3 hours, and then reduced at 180℃ for 3 hours using a 10 vol% hydrogen / argon mixture to obtain the environmentally friendly anthraquinone hydrogenation catalyst. The specific surface area of ​​the catalyst support was tested to be 282 m². 2 / g, with a pore size of 16.18nm; the environmentally friendly anthraquinone hydrogenation catalyst has a hydrogenation efficiency of 11.52g / L.

[0036] Example 5 A method for preparing an environmentally friendly anthraquinone hydrogenation catalyst includes the following steps: (1) Add aluminum nitrate and glucose to deionized water and stir until homogeneous to obtain a mixed aluminum nitrate solution; the concentration of aluminum nitrate in the mixed aluminum nitrate solution is 20 g / L; the mass ratio of glucose to aluminum nitrate is 0.2:1; (2) Add sodium aluminate and branched polyethyleneimine PEI 800 to deionized water and stir until homogeneous to obtain a sodium aluminate mixed solution; the mass ratio of branched polyethyleneimine to glucose is 0.2:1; the concentration of sodium aluminate in the sodium aluminate mixed solution is 12 g / L; the mass ratio of sodium aluminate to aluminum nitrate in step (1) is 0.75:1; (3) First, heat the aluminum nitrate mixed solution to 62°C, and while stirring, add the sodium aluminate mixed solution dropwise to the aluminum nitrate mixed solution at a rate of 10 mL / min to obtain the final solution, and adjust the pH of the final solution to 10; heat the reaction at 85°C for 2 h, then filter, wash, dry, and calcine at 600°C for 5 h to obtain the catalyst support; (4) Prepare a palladium salt solution with a palladium loading of 0.2 wt% in the catalyst support. Specifically, disperse palladium acetate in acetone to obtain a palladium salt solution, and then impregnate the catalyst support with the palladium salt solution using an equal volume impregnation process. (5) The impregnated catalyst support was dried at 110℃, calcined at 340℃ for 3 hours, and then reduced at 180℃ for 3 hours using a 10 vol% hydrogen / argon mixture to obtain the environmentally friendly anthraquinone hydrogenation catalyst. The specific surface area of ​​the catalyst support was tested to be 287 m². 2 / g, with a pore size of 17.45nm; the environmentally friendly anthraquinone hydrogenation catalyst has a hydrogenation efficiency of 11.93g / L.

[0037] Example 6 A method for preparing an environmentally friendly anthraquinone hydrogenation catalyst includes the following steps: (1) Add aluminum nitrate and glucose to deionized water and stir until homogeneous to obtain a mixed aluminum nitrate solution; the concentration of aluminum nitrate in the mixed aluminum nitrate solution is 20 g / L; the mass ratio of glucose to aluminum nitrate is 0.16:1; (2) Add sodium aluminate and branched polyethyleneimine PEI 3000 to deionized water and stir until homogeneous to obtain a sodium aluminate mixed solution; the mass ratio of branched polyethyleneimine to glucose is 0.14:1; the concentration of sodium aluminate in the sodium aluminate mixed solution is 12 g / L; the mass ratio of sodium aluminate to aluminum nitrate in step (1) is 0.75:1; (3) First, heat the aluminum nitrate mixed solution to 62°C, and while stirring, add the sodium aluminate mixed solution dropwise to the aluminum nitrate mixed solution at a rate of 10 mL / min to obtain the final solution, and adjust the pH of the final solution to 10.5; heat the reaction at 84°C for 2.2 h, then filter, wash, dry, and calcine at 610°C for 4.5 h to obtain the catalyst support; (4) Prepare a palladium salt solution with a palladium loading of 0.2 wt% in the catalyst support. Specifically, disperse palladium acetate in acetone to obtain a palladium salt solution, and then impregnate the catalyst support with the palladium salt solution using an equal volume impregnation process. (5) The impregnated catalyst support was dried at 110℃, calcined at 320℃ for 3.5h, and then reduced at 180℃ for 3h using a 10 vol% hydrogen / argon mixture to obtain the environmentally friendly anthraquinone hydrogenation catalyst. The specific surface area of ​​the catalyst support was tested to be 285 m². 2 / g, with a pore size of 16.82nm; the environmentally friendly anthraquinone hydrogenation catalyst has a hydrogenation efficiency of 12.26g / L.

[0038] Example 7 A method for preparing an environmentally friendly anthraquinone hydrogenation catalyst includes the following steps: (1) Add aluminum nitrate and glucose to deionized water and stir until homogeneous to obtain a mixed aluminum nitrate solution; the concentration of aluminum nitrate in the mixed aluminum nitrate solution is 20 g / L; the mass ratio of glucose to aluminum nitrate is 0.2:1; (2) Add sodium aluminate and branched polyethyleneimine (a mixture of PEI 800 and PEI 1800 in a mass ratio of 1:1) to deionized water and stir until homogeneous to obtain a sodium aluminate mixed solution; the mass ratio of branched polyethyleneimine to glucose is 0.2:1; the concentration of sodium aluminate in the sodium aluminate mixed solution is 12 g / L; the mass ratio of sodium aluminate to aluminum nitrate in step (1) is 0.75:1; (3) First, heat the aluminum nitrate mixed solution to 62°C, and while stirring, add the sodium aluminate mixed solution dropwise to the aluminum nitrate mixed solution at a rate of 10 mL / min to obtain the final solution, and adjust the pH of the final solution to 10; heat the reaction at 85°C for 2 h, then filter, wash, dry, and calcine at 600°C for 5 h to obtain the catalyst support; (4) Prepare a palladium salt solution with a palladium loading of 0.2 wt% in the catalyst support. Specifically, disperse palladium acetate in acetone to obtain a palladium salt solution, and then impregnate the catalyst support with the palladium salt solution using an equal volume impregnation process. (5) The impregnated catalyst support was dried at 110℃, calcined at 340℃ for 3 hours, and then reduced at 180℃ for 3 hours using a 10 vol% hydrogen / argon mixture to obtain the environmentally friendly anthraquinone hydrogenation catalyst. The specific surface area of ​​the catalyst support was tested to be 295 m². 2 / g, with a pore size of 17.88nm; the environmentally friendly anthraquinone hydrogenation catalyst has a hydrogenation efficiency of 12.89g / L.

[0039] Example 8 A method for preparing an environmentally friendly anthraquinone hydrogenation catalyst includes the following steps: (1) Add aluminum nitrate and glucose to deionized water and stir until homogeneous to obtain a mixed aluminum nitrate solution; the concentration of aluminum nitrate in the mixed aluminum nitrate solution is 20 g / L; the mass ratio of glucose to aluminum nitrate is 0.23:1; (2) Add sodium aluminate and branched polyethyleneimine PEI 600 to deionized water and stir until homogeneous to obtain a sodium aluminate mixed solution; the mass ratio of branched polyethyleneimine to glucose is 0.18:1; the concentration of sodium aluminate in the sodium aluminate mixed solution is 12 g / L; the mass ratio of sodium aluminate to aluminum nitrate in step (1) is 0.75:1; (3) First, heat the aluminum nitrate mixed solution to 62°C, and while stirring, add the sodium aluminate mixed solution dropwise to the aluminum nitrate mixed solution at a rate of 10 mL / min to obtain the final solution, and adjust the pH of the final solution to 10.5; heat the reaction at 88°C for 2.5 h, then filter, wash, dry, and calcine at 620°C for 6 h to obtain the catalyst support; (4) Prepare a palladium salt solution with a palladium loading of 0.2 wt% in the catalyst support. Specifically, disperse palladium acetate in acetone to obtain a palladium salt solution, and then impregnate the catalyst support with the palladium salt solution using an equal volume impregnation process. (5) The impregnated catalyst support was dried at 110℃, calcined at 330℃ for 4 hours, and then reduced at 180℃ for 3 hours using a 10 vol% hydrogen / argon mixture to obtain the environmentally friendly anthraquinone hydrogenation catalyst. The specific surface area of ​​the catalyst support was tested to be 292 m². 2 / g, with a pore size of 17.14nm; the environmentally friendly anthraquinone hydrogenation catalyst has a hydrogenation efficiency of 11.88g / L.

[0040] Example 9 A method for preparing an environmentally friendly anthraquinone hydrogenation catalyst includes the following steps: (1) Add aluminum nitrate and glucose to deionized water and stir until homogeneous to obtain a mixed aluminum nitrate solution; the concentration of aluminum nitrate in the mixed aluminum nitrate solution is 20 g / L; the mass ratio of glucose to aluminum nitrate is 0.18:1; (2) Add sodium aluminate and branched polyethyleneimine PEI 1200 to deionized water and stir until homogeneous to obtain a sodium aluminate mixed solution; the mass ratio of branched polyethyleneimine to glucose is 0.16:1; the concentration of sodium aluminate in the sodium aluminate mixed solution is 12 g / L; the mass ratio of sodium aluminate to aluminum nitrate in step (1) is 0.75:1; (3) First, heat the aluminum nitrate mixed solution to 62°C, and while stirring, add the sodium aluminate mixed solution dropwise to the aluminum nitrate mixed solution at a rate of 10 mL / min to obtain the final solution, and adjust the pH of the final solution to 10; heat the reaction at 83°C for 2.7 h, then filter, wash, dry, and calcine at 630°C for 5 h to obtain the catalyst support; (4) Prepare a palladium salt solution with a palladium loading of 0.2 wt% in the catalyst support. Specifically, disperse palladium acetate in acetone to obtain a palladium salt solution, and then impregnate the catalyst support with the palladium salt solution using an equal volume impregnation process. (5) The impregnated catalyst support was dried at 110℃, calcined at 310℃ for 3.5h, and then reduced at 180℃ for 3h using a 10 vol% hydrogen / argon mixture to obtain the environmentally friendly anthraquinone hydrogenation catalyst. The specific surface area of ​​the catalyst support was tested to be 286 m². 2 / g, with a pore size of 17.03nm; the environmentally friendly anthraquinone hydrogenation catalyst has a hydrogenation efficiency of 11.97g / L.

[0041] Example 10 A method for preparing an environmentally friendly anthraquinone hydrogenation catalyst includes the following steps: (1) Add aluminum nitrate and glucose to deionized water and stir until homogeneous to obtain a mixed aluminum nitrate solution; the concentration of aluminum nitrate in the mixed aluminum nitrate solution is 20 g / L; the mass ratio of glucose to aluminum nitrate is 0.2:1; (2) Add sodium aluminate and branched polyethyleneimine PEI 1800 to deionized water and stir until homogeneous to obtain a sodium aluminate mixed solution; the mass ratio of branched polyethyleneimine to glucose is 0.2:1; the concentration of sodium aluminate in the sodium aluminate mixed solution is 12 g / L; the mass ratio of sodium aluminate to aluminum nitrate in step (1) is 0.75:1; (3) First, heat the aluminum nitrate mixed solution to 62°C, and while stirring, add the sodium aluminate mixed solution dropwise to the aluminum nitrate mixed solution at a rate of 10 mL / min to obtain the final solution, and adjust the pH of the final solution to 10; heat the reaction at 85°C for 2 h, then filter, wash, dry, and calcine at 600°C for 5 h to obtain the catalyst support; (4) Prepare a palladium salt solution with a palladium loading of 0.2 wt% in the catalyst support. Specifically, disperse palladium acetate in acetone to obtain a palladium salt solution, and then impregnate the catalyst support with the palladium salt solution using an equal volume impregnation process. (5) The impregnated catalyst support was dried at 110℃, calcined at 340℃ for 3 hours, and then reduced at 180℃ for 3 hours using a 10 vol% hydrogen / argon mixture to obtain the environmentally friendly anthraquinone hydrogenation catalyst. The specific surface area of ​​the catalyst support was tested to be 290 m². 2 / g, with a pore size of 17.22nm; the environmentally friendly anthraquinone hydrogenation catalyst has a hydrogenation efficiency of 12.31g / L.

[0042] Comparative Example 1 A method for preparing an environmentally friendly anthraquinone hydrogenation catalyst includes the following steps: (1) Add aluminum nitrate and branched polyethyleneimine PEI 1800 to deionized water and stir until homogeneous to obtain a mixed aluminum nitrate solution; the concentration of aluminum nitrate in the mixed aluminum nitrate solution is 20 g / L; (2) Add sodium aluminate and glucose to deionized water and stir until homogeneous to obtain a sodium aluminate mixed solution; the mass ratio of glucose to aluminum nitrate is 0.2:1; the mass ratio of branched polyethyleneimine to glucose is 0.2:1; the concentration of sodium aluminate in the sodium aluminate mixed solution is 12 g / L; the mass ratio of sodium aluminate to aluminum nitrate in step (1) is 0.75:1; (3) First, heat the aluminum nitrate mixed solution to 62°C, and while stirring, add the sodium aluminate mixed solution dropwise to the aluminum nitrate mixed solution at a rate of 10 mL / min to obtain the final solution, and adjust the pH of the final solution to 10; heat the reaction at 85°C for 2 h, then filter, wash, dry, and calcine at 600°C for 5 h to obtain the catalyst support; (4) Prepare a palladium salt solution with a palladium loading of 0.2 wt% in the catalyst support. Specifically, disperse palladium acetate in acetone to obtain a palladium salt solution, and then impregnate the catalyst support with the palladium salt solution using an equal volume impregnation process. (5) The impregnated catalyst support was dried at 110℃, calcined at 340℃ for 3 hours, and then reduced at 180℃ for 3 hours using a 10 vol% hydrogen / argon mixture to obtain the environmentally friendly anthraquinone hydrogenation catalyst. The specific surface area of ​​the catalyst support was tested to be 236 m². 2 / g, with a pore size of 11.21nm; the environmentally friendly anthraquinone hydrogenation catalyst has a hydrogenation efficiency of 8.32g / L.

[0043] Comparative Example 2 A method for preparing an environmentally friendly anthraquinone hydrogenation catalyst includes the following steps: (1) Add aluminum nitrate and glucose to deionized water and stir until homogeneous to obtain a mixed aluminum nitrate solution; the concentration of aluminum nitrate in the mixed aluminum nitrate solution is 20 g / L; the mass ratio of glucose to aluminum nitrate is 0.2:1; (2) Add sodium aluminate and branched polyethyleneimine PEI 1800 to deionized water and stir until homogeneous to obtain a sodium aluminate mixed solution; the mass ratio of branched polyethyleneimine to glucose is 0.4:1; the concentration of sodium aluminate in the sodium aluminate mixed solution is 12 g / L; the mass ratio of sodium aluminate to aluminum nitrate in step (1) is 0.75:1; (3) First, heat the aluminum nitrate mixed solution to 62°C, and while stirring, add the sodium aluminate mixed solution dropwise to the aluminum nitrate mixed solution at a rate of 10 mL / min to obtain the final solution, and adjust the pH of the final solution to 10; heat the reaction at 85°C for 2 h, then filter, wash, dry, and calcine at 600°C for 5 h to obtain the catalyst support; (4) Prepare a palladium salt solution with a palladium loading of 0.2 wt% in the catalyst support. Specifically, disperse palladium acetate in acetone to obtain a palladium salt solution, and then impregnate the catalyst support with the palladium salt solution using an equal volume impregnation process. (5) The impregnated catalyst support was dried at 110℃, calcined at 340℃ for 3 hours, and then reduced at 180℃ for 3 hours using a 10 vol% hydrogen / argon mixture to obtain the environmentally friendly anthraquinone hydrogenation catalyst. The specific surface area of ​​the catalyst support was tested to be 244 m². 2 / g, with a pore size of 11.75nm; the environmentally friendly anthraquinone hydrogenation catalyst has a hydrogenation efficiency of 9.21g / L.

[0044] As can be seen from Examples 1-10 and Comparative Examples 1-2 above, this invention uses inexpensive and readily available glucose as a template agent and adds branched polyethyleneimine as an auxiliary agent to solve the defects of low specific surface area and small pore size of alumina support prepared with small molecule glucose as template. It successfully prepared a catalyst support with a high specific surface area. Using this support to impregnate with palladium significantly reduces the preparation cost of anthraquinone hydrogenation catalyst. It also has the advantages of simple and green preparation process and is easy to scale up.

[0045] Specifically, compared to Example 10, Comparative Example 1, which added glucose to a sodium aluminate solution and branched polyethyleneimine to an aluminum nitrate solution, showed deterioration in both catalyst support performance and the performance of the environmentally friendly anthraquinone hydrogenation catalyst. This is because when glucose is added to a sodium aluminate solution, its function as a primary template agent is weakened, failing to effectively guide the formation of mesopores. Simultaneously, when branched polyethyleneimine is added to an aluminum nitrate solution, both the branched polyethyleneimine and aluminum species are positively charged, resulting in electrostatic repulsion rather than attraction. This electrostatic repulsion prevents the branched polyethyleneimine from effectively adsorbing aluminum ions, thus failing to guide the deposition of aluminum precursors at the molecular level. The spatial spacing and pore-expanding functions of the branched polyethyleneimine as an auxiliary agent cannot be realized. Neither template agent can effectively pre-assemble with its respective compatible aluminum source before precipitation. Ultimately, the co-precipitation process degenerates into disordered random deposition, failing to effectively improve the specific surface area and pore size of the support. Compared to Example 10, Comparative Example 2, which used too much branched polyethyleneimine relative to glucose, also showed a downward trend in performance. This is because when branched polyethyleneimine is in excess relative to glucose, the densely packed amino groups on its molecular chain have strong electrostatic and hydrogen bonding interactions with the aluminum precursor and glucose. Branched polyethyleneimine tends to preferentially adsorb aluminum species and dominate the deposition process. This weakens the relative role of the glucose template, destroys the mesoporous structure originally guided by glucose, and results in poor stability. During calcination, it collapses, which is detrimental to increasing the specific surface area and leads to a decrease in catalytic performance.

[0046] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. For those skilled in the art, other variations or modifications can be made based on the above description. It is impossible to exhaustively list all the implementation methods here. All obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing an environmentally friendly anthraquinone hydrogenation catalyst, characterized in that, Includes the following steps: (1) Add aluminum salt and glucose to deionized water and stir until homogeneous to obtain a mixed aluminum salt solution; (2) Add aluminate and branched polyethyleneimine to deionized water and stir until homogeneous to obtain a mixed solution of aluminate; the mass ratio of branched polyethyleneimine to glucose is (0.1-0.25):1; (3) While stirring, add the aluminate mixed solution dropwise to the aluminum salt mixed solution to obtain the final solution, and adjust the pH of the final solution to be alkaline; The alumina catalyst support is obtained by heating and reacting, followed by filtration, washing, drying, and calcination. (4) Disperse palladium salt in a solvent to obtain a palladium salt solution, and then impregnate the alumina catalyst support with the palladium salt solution; (5) The impregnated alumina catalyst support is dried, calcined and reduced to obtain an environmentally friendly anthraquinone hydrogenation catalyst.

2. The method for preparing an environmentally friendly anthraquinone hydrogenation catalyst as described in claim 1, characterized in that, In step (1), the aluminum salt is at least one of aluminum nitrate, aluminum chloride, and aluminum sulfate.

3. The method for preparing an environmentally friendly anthraquinone hydrogenation catalyst as described in claim 1, characterized in that, In step (1), the mass ratio of glucose to aluminum salt is (0.1-0.3):

1.

4. The method for preparing an environmentally friendly anthraquinone hydrogenation catalyst as described in claim 1, characterized in that, In step (2), the aluminate is at least one of sodium aluminate or potassium aluminate.

5. The method for preparing an environmentally friendly anthraquinone hydrogenation catalyst as described in claim 1, characterized in that, The mass ratio of aluminate in step (2) to aluminum salt in step (1) is (0.1-1):

1.

6. The method for preparing an environmentally friendly anthraquinone hydrogenation catalyst as described in claim 1, characterized in that, The pH value in step (3) is 8-11.

7. The method for preparing an environmentally friendly anthraquinone hydrogenation catalyst as described in claim 1, characterized in that, In step (4), the palladium salt is at least one of palladium chloride, palladium nitrate, and palladium acetate.

8. The method for preparing an environmentally friendly anthraquinone hydrogenation catalyst as described in claim 1, characterized in that, The drying temperature in step (5) is 100-130℃.

9. The method for preparing an environmentally friendly anthraquinone hydrogenation catalyst as described in claim 1, characterized in that, In step (5), the roasting temperature is 300-350℃ and the roasting time is 3-4h.

10. An environmentally friendly anthraquinone hydrogenation catalyst, characterized in that, It is prepared by the method for preparing an environmentally friendly anthraquinone hydrogenation catalyst according to any one of claims 1-9.

Citation Information

Patent Citations

  • Anthraquinone hydrogenation catalyst as well as preparation method and application thereof

    CN112717925A

  • Palladium catalyst for anthraquinone hydrogenation and preparation method thereof

    CN120438003A

  • Alumina-based catalyst for anthraquinone hydrogenation and preparation method thereof

    CN120515404A

  • Preparation method of bulk phase hydrogenation catalyst

    CN114073962A

  • Method for preparing catalyst supports and supported catalysts from single walled carbon nanotubes

    US20060137817A1